A Test of Pollution Haven Hypothesis (PHH) in the Environmental Kuznets Curve (EKC) Framework in Selected ASEAN Countries (Journal of Governance and Development (JGD), 2023)
The underlying study focuses on Pollution Haven Hypothesis (PHH) from thetrade perspective for the Association of South East Asian Nations (ASEAN)countries for the period 1989 -2015. The PHH claims that in open traderegime developing countries tend to specialize and export pollution-intensivegoods. This study examines this proposition in the context of ASEAN versusUnited states of America (USA) trade. The results indicate that exportsof pollution-intensive- goods from ASEAN countries to USA significantlycontribute to the pollution thereby, delaying the turning point income levelof the EKC in ASEAN countries. The study, therefore, concludes that worldpollution cannot be tackled unless advanced countries do not curtail theconsumption of pollution-intensive goods.